Pengaruh Pendapatan Terhadap ROA BRI Syariah (Periode 2011-2016) - Erwin Januarta; Fadilla Fadilla (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2018)
This study aims to see the effect of income on ROA BRI Syariah. This research is an associative study with a quantitative approach. The data analysis technique used simple linear regression with a random effects model. The data used are secondary data in the form of monthly financial ratios with a total of 70 observations. Data collection is taken by using documentation technique which is sourced from bank publication reports. Sampling was done by purposive sampling with a number of 1 bank. The object in this study is BRI Syariah. The dependent variable in this study is ROA (Return On Assets) while the independent variable in this study is revenue sharing on musharaka. The results showed that there was an influence between musyarakah income on the profitability of BRI Syariah. the significance value of the t test is 0.012. This value is <than 0.005. Which means that there is an influence between musharaka on ROA. In the output of the above spss, it can be seen that the significance value is 0.012. <from 0.05 means that there is an influence of musharaka on ROA